Penerapan Datamining Klasifikasi Pada Faktor Pemilihan Cafe Bagi Anak Millineal - Tanjung, Fatimah Dwi Puspa; Windarto, Agus Perdana; Irawan, Eka (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The purpose of this study is to apply the cafe selection factor for millennial children at the Sutomo Square cafe Pematangsiantar City by using the C4.5 Algorithm. Sources of data in the study used were observations, literature studies and distributing questionnaires to millennial children at the Sutomo Square cafe, Pematangsiantar City. The results of this study are expected to determine the factors in the selection of cafes for millennial children so that cafe owners can improve their creativity and cafe quality